2011
DOI: 10.1038/ncomms1419
|View full text |Cite
|
Sign up to set email alerts
|

Advantageous grain boundaries in iron pnictide superconductors

Abstract: High critical temperature superconductors have zero power consumption and could be used to produce ideal electric power lines. The principal obstacle in fabricating superconducting wires and tapes is grain boundaries—the misalignment of crystalline orientations at grain boundaries, which is unavoidable for polycrystals, largely deteriorates critical current density. Here we report that high critical temperature iron pnictide superconductors have advantages over cuprates with respect to these grain boundary iss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
277
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 270 publications
(292 citation statements)
references
References 43 publications
10
277
5
Order By: Relevance
“…[9] Compared to cuprates, the properties of iron-pnictide Josephson-junction devices remain inferior due largely to their metallic characters. However, their superior grain boundary properties [10] along with high upper critical magnetic fields (H c2 ) ≥ 50 T and small anisotropic factors γ = H c2 //ab / H c2 //c = 1-2 [11] are promising for wire [12][13][14] and tape applications. [15,16] Similar to cuprates, the extrinsic pinning centers largely control J c in iron pnictides.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Compared to cuprates, the properties of iron-pnictide Josephson-junction devices remain inferior due largely to their metallic characters. However, their superior grain boundary properties [10] along with high upper critical magnetic fields (H c2 ) ≥ 50 T and small anisotropic factors γ = H c2 //ab / H c2 //c = 1-2 [11] are promising for wire [12][13][14] and tape applications. [15,16] Similar to cuprates, the extrinsic pinning centers largely control J c in iron pnictides.…”
Section: Introductionmentioning
confidence: 99%
“…The early results indicate that the global critical current is limited by intergrain currents over the grain boundaries in polycrystalline bulk and wires [12][13][14][15][16][17][18]. Recent experiments revealed that high-angle grain boundary largely deteriorates critical current density J c in Ba(Fe 1-x Co x ) 2 As 2 bicrystals [19,20]. These results suggest that the discovered iron based superconductors are exhibiting weak link grain boundary behavior similar to high-T c cuprate superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…T he reasonably high values of the superconducting transition temperature T c , very high upper critical magnetic fields and generally low anisotropy of the recently discovered iron-based superconductors [1][2][3] enable operation in economically interesting temperature-field ranges and, at the same time, minimize detrimental effects due to grain boundaries and thermal fluctuations 4,5 . However, the overriding application metric, the maximum loss-less electrical current density, is ultimately determined by the vortex pinning that can be engineered into the material.…”
mentioning
confidence: 99%